A Note on Time-motion Study in Saw Milling - Rawat, B. S.; Bhatnagar, R. C. (Indian Forester, 1973)
Time-motion studies were carried out on a Horizontal Log Band Mill in a local Saw Mill. The study covered 74 Sal (Shorea robusta) logs. Observations for various time elements were recorded. Percentages or various time elements with respect to total time and relationships obtained between cutting area and cutting time and between volume of log and total sawing time are described in the present paper.